The need for detailed gender-specific occupational safety analysis. (September 2017) - Cruz Rios, Fernanda; Chong, Wai K.; Grau, David
Abstract: Introduction: The female work in population is growing in the United States, therefore the occupational health and safety entities must start to analyze gender-specific data related to every industry, especially to nontraditional occupations. Women working in nontraditional jobs are often exposed to extreme workplace hazards. These women have their safety and health threatened because there are no adequate policies to mitigate gender-specific risks such as discrimination and harassment. Employers tend to aggravate this situation because they often fail to provide proper reporting infrastructure and support. According to past studies, women suffered from workplace injuries and illnesses that were less prominent among men. Statistics also confirmed that men and women faced different levels of risks in distinct work environments. For example, the rates of workplace violence and murders by personal acquaintances were significantly higher among women. Methods: In this paper, the authors analyze prior public data on fatal and nonfatal injuries to understand why we need to differentiate genders when analyzing occupational safety and health issues. Results: The analyses confirmed that women dealt with unique workplace hazards compared to men. Conclusions: It is urgent that public agencies, such as the U.S. Department of Labor, record gender-specific data in details and by occupations and industries. Practical application: The reader will become aware of the current lack – and need – of data and knowledge about injuries and illnesses separated by gender and industry. Finally, safety and health researchers are encouraged to investigate the gender-specific data in all industries and occupations, as soon as they become available. Highlights: Men and women faced different levels of workplace safety risks, especially in nontraditional occupations for women; Workplace violence with female victims increased over the last years. The trend was opposite for male victims; Women were killed in their workplaces twice more often than men, and homicides were more common in jobs with more women Relatives and other acquaintances committed 25% of women's homicides and 3% of men's homicides. Gendered injuries and illnesses data and analyses are urgently needed.